Fungal Pathogens Associated with Vascular Streak Dieback (VSD) Disease on Cacao in Special Region of Yogyakarta Province - Hendra Hendra; Arif Wibowo; Suryanti Suryanti (Jurnal Perlindungan Tanaman Indonesia, 2019)
Cacao is one of the pre-eminent crops plantation with high economic value. Indonesia's cacao beans production is the third largest in the world after Ivory Coast and Ghana. Vascular Streak Dieback (VSD) is one of the important diseases of cacao which caused a decreased yield either in quantity or quality. The disease is caused by the basidiomycete fungus Ceratobasidium theobromae (syn. Oncobasidium theobromae). Spores are carried by wind to spread, infect young leaves and penetrate through natural openings and colonize xylem vessel which could inhibit the transportation system in the plant tissue. There are several fungal pathogens associated with VSD diseases on cacao. This research aimed to study the fungi associate with VSD diseases on cacao in Special Region of Yogyakarta Province. Survey and sampling were conducted in cacao plantations in regencies of Gunungkidul, Kulon Progo, Bantul and Sleman. The severity of VSD disease in the regencies of Gunungkidul and Kulon Progo were high, while in the regencies of Sleman and Bantul were moderate. Eighty eight fungal isolates were isolated from infected petiole and stem. The in vitro pathogenicity test screened 32 fungal isolates causing necrotic and chlorotic symptoms on young healthy cacao leaves with and without wounding. The first symptoms appeared at 8-12 days after inoculation and fungal mycelium could grow at 1−3 days after inoculation. Those isolates collected showed a high diversity of colony morphology. Lasiodiplodia sp., Fusarium sp., Colletotrichum sp., and Pestalotiopsis sp. had been identified based on conidial morphology.